Nilai Nilai Pendidikan Agama Islam Dalam Pembiasaan Kesamaptaan Dan Religi Kelas X SMK Negeri 1 Bawen Tahun 2025/2026 - Hanik, Asbi' Mufarokhatul; Matori, Matori; Rosidi, Ayep (Universitas Muhammadiyah Magelang, 2026)
This study wants to look at how Islamic religious values are taught through students' physical fitness and religious habit programs. This research employed a descriptive qualitative method. Data was gathered by observing, having detailed conversations, and keeping records. Data analysis was done by reducing data, showing data, and drawing conclusions, using multiple sources and methods to check the results. The results show that habituation helps to instill values like faith, worship, morality, discipline, responsibility, hard work, and spirituality. The study finds that this habituation model works well as a way to build character education using Islamic values..